Hip Dysplasia Is Not More Common in W-Sitters. (October 2020) - Rethlefsen, Susan A.; Mueske, Nicole M.; Nazareth, Alexander; Abousamra, Oussama; Wren, Tishya A. L.; Kay, Robert M.; Goldstein, Rachel Y.
Parents are frequently cautioned by therapists, teachers, physicians, and online resources about potential negative effects of w-sitting in children (including hip dysplasia), despite lack of evidence. To examine relationships between w-sitting and hip dysplasia, a prospective cohort study was conducted of 104 patients (196 hips), aged 9.9 (standard deviation = 5.7) years, who underwent hip/pelvis radiography at a pediatric tertiary care center. Measures of hip dysplasia were taken from radiographs. Parents/patients completed a questionnaire regarding the patients' sitting habits. Associations between hip dysplasia and w-sitting were analyzed statistically. About 48/104 parents/patients (46%) reported current or past w-sitting: 11/104 (11%) current, preferred position; 23/104 (22%) current, nonpreferred position, 14/104 (13%) w-sat in past, and 56/104 (54%) never w-sat. There was no difference in measures of hip dysplasia ( P > .12) or hip dysplasia frequency between w-sitters (9%) and non-w-sitters (10%; P = .81), or among w-sitting persistence groups ( P = .26). W-sitting in children is not associated with hip dysplasia.